Application of Artificial Fish Apartments to Enhance Fish Communities in the Waters around Tanjungjati B Power Plant, Jepara, Central Java - Munasik; Arbanto, Bonifacius; Nurrasyid Chamidy, Ardian; Nashihi Aufar, Syauqina; Wibawa NS, Ari; Agung Prabowo, Handoko; Mustagfirin; Azizah, Nur (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2025)
The decline in fish stocks, resulting from habitat degradation and overfishing, has become a significant threat to the sustainability of fisheries in Indonesia. One of the efforts to support ecosystem recovery and improve fishermen’s catches is the application of artificial fish apartments. This study aims to analyse the implementation process and effectiveness of artificial fish apartments in the waters around the Tanjung Jati B Power Plant in Jepara. The programs were carried out through a participatory approach with local fishing communities, including socialization, scuba diving training, concrete module construction, installation, and evaluation. A total of five artificial fish apartment units were installed at two sites, namely Karang Pringitan (3 units) and Karang Ketapang (2 units). Evaluation three months after installation showed an increase in fish communities, with 16 species recorded at Karang Pringitan and 9 species at Karang Ketapang. These results confirm that artificial fish apartments can serve as new habitats for pelagic and target fish species and have the potential to support the sustainability of local fisheries.